Genital Mycoplasmas and Biomarkers of Inflammation and Their Association With Spontaneous Preterm Birth and Preterm Prelabor Rupture of Membranes: A Systematic Review and Meta-Analysis - Noda-Nicolau, Nathalia M.; Tantengco, Ourlad Alzeus G.; Polettini, Jossimara; Silva, Mariana C.; Bento, Giovana F. C.; Cursino, Geovanna C.; Marconi, Camila; Lamont, Ronald F.; Taylor, Brandie D.; Silva, Márcia G.; Jupiter, Daniel; Menon, Ramkumar (Frontiers in Microbiology, 2022)
Genital mycoplasmas (GM), such as Mycoplasma hominis, Mycoplasma genitalium, Ureaplasma parvum, and Ureaplasma urealyticum are commonly associated with spontaneous preterm labor (SPTL), spontaneous preterm birth (PTB), and preterm prelabor rupture of membranes (PPROM). This study determined the association between GM and adverse pregnancy outcomes. We searched for studies published 1980-2019 in MEDLINE, EMBASE, and Web of Science. Studies were eligible when GM was detected during pregnancy. We included 93 and 51 studies in determining the prevalence and the inflammatory biomarkers associated with GM, respectively, using the "metafor" package within R. The protocol was registered with PROSPERO (registration no. CRD42016047297). Women with adverse pregnancy outcomes had significantly higher odds of colonization with GM compared to women who delivered at term. For PTB, the odds ratios were: M. hominis (OR: 2.25; CI: 1.35 – 3.75; I2: 44%), M. genitalium (OR: 2.04; CIL 1.18 – 3.53; I2: 20%), U. parvum (OR: 1.75; CI: 1.47 – 2.07; I2: 0%), U. urealyticum (OR: 1.50; CI: 1.08 – 2.07; I2: 58%). SPTL had significantly higher odds with M. hominis (OR: 1.96; CI: 1.19 – 3.23; I2: 1%) or U. urealyticum (OR: 2.37; CI: 1.20 – 4.70; I2: 76%) compared to women without SPTL. Women with PPROM had significantly higher odds with M. hominis (OR: 2.09; CI: 1.42 – 3.08; I2: 0%) than women without PPROM. However, our subgroup analysis based on the diagnostic test and the specimen used for detecting GM showed a higher prevalence of GM in maternal specimens than in fetal specimens. GM colonization of the cervix and vagina was associated with lower odds of PTB and PTL. In contrast, colonization of the AF, fetal membrane, and the placenta was associated with increased odds of PTB and PTL. In conclusion, GM colonization of the fetal tissues was significantly associated with significantly increased odds of PTB and PTL. We propose that the fetal inflammatory response is the final trigger to promote GM-induced PTB, while maternal inflammation due to GM colonization helps maintain immunologic homeostasis during pregnancy and promote fetoplacental growth.